ЕARLY RESULTS OF TREATMENT WITH RADIAL EXTRACORPOREAL SHOCK WAVE THERAPY COMPARED TO CONVENTIONAL PHYSICAL THERAPY IN PATIENTS WITH KNEE OSTEOARTHRITIS - Kalchovska ivanovska, Biljana; Gocevska, Marija; Manoleva, Maja; Koevska, Valentina; Mitrevska, Biljana; GJerakaroska Savevska, Cvetanka; Nikolikj Dimitrova, Erieta; Saveski, Aleksandar (Faculty of Medicine, Ss. Cyril and Methodius University in Skopje, 2022)
Knee osteoarthritis is a common musculoskeletal disorder. Radial extracorporeal shock wave therapy (RECTUB) is as a new effective conservative method. This was a prospective, monocentric, interventional, non-randomized, controlled, clinical study that included a total of 50 patients divided into two groups. The study group was treated with RECTUB and kinesitherapy, and the control group was treated with conventional physical therapy and kinesitherapy. The patients’ progress was monitored on the Numeric scale of pain and the WOMAC Index of functional ability before the treatment started; then immediately after its completion, and finally 3 months afterwards. It was shown that patients from the study and control groups did not differ significantly in terms of pain intensity at the treatment beginning and at their first control, while the difference in pain intensity between the two groups at their second control was significantly different in favor of the study group. The total value and the values of the three subscales on the WOMAC index were insignificantly different between the two groups before the treatment from a statistical point of view, with significantly lower values thereof obtained in patients in the study group at the first and second control. The results of this study demonstrate the benefits of using RECTUB as a safe, non-invasive, conservative treatment for knee osteoarthritis with better and longer-lasting effect on reducing pain and improving the functional ability of patients with knee osteoarthritis in contrast to patients treated with conventional physical therapy.
Keywords: knee osteoarthritis; radial extracorporeal shock wave therapy